The Effect of Jamblang Leaves Extract (Syzygium cumini) Inclusion Skim Milk-Egg Yolk Extender on Motility, Abnormality and Viability of Aceh Cattle Spermatozoa Stored at 4ºC - Cut Intan Novita; Rosna Sari; Eka Meutia Sari (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
This research aimed to know the effect of the addition of jamblang leaves extract (Syzygium cumini) in skim milk-egg yolk diluent material on motility, abnormality, and viability of Aceh cattle stored at 4ºC. The research design used was Complete Randomized Design consisting of 5 treatment and 5 repetitions. The treatments consisted of J0 (SSKT), J1 (SSKT+ EDJ 0. g/ 100 ml), J2 (SSKT+ EDJ 0.4 g/ 100 ml), J3 (SSKT+ EDJ 0.6 g/ 100 ml) and J4 (SSKT+ EDJ 0.8 g/ 100 ml). The data obtained were analyzed descriptively by determining the mean value and standard deviation using Microsoft Excel. The research result indicated that the addition of jamblang leaves extract in skim milk-egg yolk diluent material maintaining the motility, viability and abnormality of the spermatozoa of Aceh cattle stored at the temperature of 4ºC. Based on the research that has been carried out, it can be concluded that the addition of jamblang leaves extract in skim milk-egg yolk diluent material can maintain the quality of Aceh cattle spermatozoa, while the use of incorrect dose becomes toxic and disrupt the spermatozoa activities to cause death.